Ammonia modified fly ash-based aerogel as well as preparation method and application thereof
Through alkali melting treatment and weak acid and weak alkali treatment of fly ash, combined with ammonia modification treatment, an ammonia modified fly ash-based aerogel suitable for large-scale production was prepared, which solved the problems of complex preparation processes and high cost in the prior art and achieved efficient carbon capture effect.
Patent Information
- Application Number
- CN202510139259.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing aerogel preparation process is complex and has high cost, which limits its further promotion and application in the field of carbon capture, and the existing fly ash-based aerogel has low carbon capture adaptability.
Fly ash is treated with alkali melting, and a fly ash-based aerogel matrix is obtained by weak acid and weak alkali treatment, which is then mixed with ammonia solution for modification, and finally an ammonia-modified fly ash-based aerogel is obtained by grading freeze-drying.
The aerogel preparation process is simplified, the cost is reduced, and the carbon capture performance is improved. It is suitable for large-scale production and is carried out under normal pressure without the need for unconventional equipment and environment.
Smart Images

Figure CN119771376A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and more specifically relates to an ammonia-modified fly ash-based aerogel and a preparation method and application thereof. Background Art
[0002] The rapid development of industry has consumed a large amount of fossil energy and caused a large amount of carbon dioxide (CO2) emissions. Carbon capture, utilization and storage technology is one of the most effective technical means to achieve the goal of "carbon peak and carbon neutrality". At present, the cost and performance of carbon capture materials are still one of the primary issues that need to be considered for the large-scale promotion and application of carbon dioxide capture technology.
[0003] Aerogel is a porous material with a three-dimensional network structure, which has the characteristics of large specific surface area, low density and high porosity. In recent years, aerogels have been widely developed in the field of CO2 capture, such as carbon aerogel, cellulose aerogel, silica aerogel, alumina aerogel, etc. However, the existing aerogel preparation process is relatively complicated and the preparation cost is high. This limits its further promotion and application in carbon capture and utilization. Therefore, the development of an aerogel with a simple synthesis process, low cost and excellent carbon capture performance is a necessary condition for achieving its high-quality development.
[0004] Fly ash is the main solid waste generated by coal-fired power plants. The accumulation of large amounts of fly ash will inevitably cause serious environmental problems. In recent years, the use of fly ash from power plants as raw materials to prepare fly ash-based aerogels has become a research hotspot in the field of industrial solid waste utilization. However, some existing methods use strong acids and organic solvents to treat fly ash raw materials, and require harsh working conditions for drying. The cumbersome process is not conducive to industrial production and application, and the prepared aerogels are less compatible with carbon capture applications. Summary of the invention
[0005] The purpose of the present invention is to provide an ammonia-modified fly ash-based aerogel and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing ammonia-modified fly ash-based aerogel, the steps comprising:
[0008] Grinding and mixing fly ash and alkali flux, and subjecting the mixture to alkali fusion treatment to obtain alkali fused fly ash product;
[0009] adding the alkali-fused fly ash product into an acid solution, stirring and hydrolyzing, and obtaining a filtrate after solid-liquid separation;
[0010] Adding urea aqueous solution to the filtrate, aging and washing, to obtain a fly ash-based aerogel matrix;
[0011] The fly ash-based aerogel matrix is mixed with an ammonia solution and subjected to a modification treatment to obtain an ammonia-modified aerogel matrix;
[0012] The ammonia-modified aerogel matrix is subjected to graded freeze drying to obtain the ammonia-modified fly ash-based aerogel.
[0013] Furthermore, the alkali flux includes at least one of sodium bicarbonate, sodium acetate, potassium acetate and magnesium carbonate.
[0014] Optionally, the alkali flux includes sodium bicarbonate, sodium acetate, potassium acetate and magnesium carbonate.
[0015] Optionally, the alkali flux includes sodium bicarbonate, sodium acetate and potassium acetate.
[0016] Optionally, the alkali flux includes potassium carbonate and magnesium carbonate.
[0017] Optionally, the alkali flux includes sodium bicarbonate and magnesium carbonate.
[0018] Optionally, the alkali flux includes sodium bicarbonate, sodium acetate and magnesium carbonate.
[0019] Furthermore, the mass ratio of the fly ash to the alkali flux is 1:1.7-1.9.
[0020] Furthermore, the temperature of the alkali fusion treatment is 650-900°C, the heating rate is 3-5°C / min, and the insulation time is 1.5-2h.
[0021] Furthermore, the acid solution includes an aqueous solution of at least one of citric acid, oxalic acid and glacial acetic acid, with a concentration of 2-4 mol / L.
[0022] Optionally, the acid solution includes a mixed solution of citric acid aqueous solution, oxalic acid aqueous solution and glacial ethyl aqueous solution.
[0023] Optionally, the acid solution includes a mixed solution of an aqueous citric acid solution and an aqueous oxalic acid solution.
[0024] Optionally, the acid solution includes a mixed solution of an oxalic acid aqueous solution and an icy ethyl aqueous solution.
[0025] Optionally, the acid solution comprises an aqueous citric acid solution.
[0026] Optionally, the acid solution comprises an aqueous oxalic acid solution.
[0027] Furthermore, the solid-to-liquid ratio (g:mL) of the alkali-fused fly ash product and the mixed acid solution is 1:5-6.
[0028] Furthermore, the stirring hydrolysis time is 4-6 hours, and the stirring rate is 180-320 rpm.
[0029] Furthermore, the concentration of the urea aqueous solution is 1.2-2.1 mol / L.
[0030] Furthermore, the volume ratio of the filtrate to the urea aqueous solution is 25:1.
[0031] Furthermore, the aging time is 5-6 hours and the temperature is 80-100°C.
[0032] Furthermore, the ammonia solution is an ethanol solution of at least one of melamine, tetraethylenepentamine and ammonium chloride, and the concentration is 0.7-0.9 mol / L.
[0033] Optionally, the ammonia solution is a mixed solution of melamine ethanol solution, tetraethylene pentamine ethanol solution and ammonium chloride ethanol solution.
[0034] Optionally, the ammonia solution is a mixed solution of melamine ethanol solution and tetraethylenepentamine ethanol solution.
[0035] Optionally, the ammonia solution is a mixed solution of tetraethylenepentamine ethanol solution and ammonium chloride ethanol solution.
[0036] Optionally, the ammonia solution is a tetraethylenepentamine ethanol solution.
[0037] Furthermore, the solid-to-liquid ratio (g:mL) of the fly ash-based aerogel matrix to the mixed ammonia solution is 1:4.
[0038] Furthermore, the step of graded freeze-drying includes: freezing at -30°C to -40°C for 6-8 hours, and then freezing at -60°C to -70°C for 24-30 hours.
[0039] The second technical solution of the present invention is to provide an ammonia-modified fly ash-based aerogel, wherein the ammonia-modified fly ash-based aerogel is prepared by the above-mentioned preparation method.
[0040] The third technical solution of the present invention is to provide an application of the above-mentioned ammonia-modified fly ash-based aerogel in carbon dioxide capture.
[0041] The present invention discloses the following technical effects:
[0042] The method for preparing ammonia-modified fly ash-based aerogels provided by the invention is simple, easy to operate, and suitable for large-scale production and application. The prepared ammonia-modified fly ash-based aerogels have good carbon capture effect.
[0043] The present invention does not use strong corrosive chemicals such as strong acids and strong alkalis in the aerogel preparation process, and innovatively proposes to use weak acids and weak alkalis to treat fly ash to obtain a fly ash-based aerogel matrix with excellent physical and chemical properties. The solvent used has the characteristics of mild reaction conditions and safety, and is easy to promote and implement.
[0044] The fly ash-based aerogel prepared by the present invention is all carried out under normal pressure, without the use of unconventional special equipment, without the need for harsh and specific unconventional environment, and has a simple process, convenient operation and easy control.
[0045] The present invention uses fly ash, a solid waste from power plants, as raw material, has a huge output, is cheap and easily available, has a low production cost, is suitable for mass production, and applies fly ash to the field of carbon capture technology, which is significantly innovative.
[0046] The physical and chemical property analysis of the fly ash-based aerogel prepared by the present invention and the carbon dioxide capture test results show that the synthesized ammonia-modified fly ash-based aerogel has excellent carbon dioxide capture effect, providing a feasible solution for the development of low-cost and high-efficiency carbon capture technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0048] Figure 1 This is the X-ray diffraction pattern of the ammonia-modified fly ash-based aerogel prepared in Example 1.
[0049] Figure 2 This is the SEM image of the ammonia-modified fly ash-based aerogel prepared in Example 1. DETAILED DESCRIPTION
[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0051] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0055] Unless otherwise specified, room temperature and normal temperature in the specific embodiments of the present invention refer to 20-30°C.
[0056] The raw materials and reagents used in the present invention are all commercially available products.
[0057] The fly ash used in the specific implementation scheme of the present invention is provided by Jilin Thermal Power Plant Company, and its main components are shown in Table 1.
[0058] Table 1 Main components of fly ash
[0059]
[0060] Example 1
[0061] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0062] S1. Weigh 6g of sodium bicarbonate, 12g of sodium acetate, 9g of potassium acetate and 9g of magnesium carbonate respectively to prepare an alkali flux, then weigh 20g of fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to the alkali melting temperature of 750°C at a heating rate of 4°C / min, and keep the temperature constant for 2h to obtain an alkali-fused fly ash product;
[0063] S2, weigh 5g of alkali-fused fly ash product and add it to 25mL of a mixed acid solution of 2mol / L of citric acid, oxalic acid and glacial acetic acid (the mass ratio of the three is 4:2:1), stir at room temperature for 5h, and stir at a rate of 180rpm, then separate the solid and liquid to obtain a filtrate;
[0064] S3, weighing 1 mL of 1.8 mol / L urea aqueous solution and adding it to the filtrate obtained in step S2, then placing it in a constant temperature drying oven at 90° C. for gel aging for 6 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0065] S4, weighing 5 g of fly ash-based aerogel, adding it to 20 mL of a mixed ammonia solution of 0.8 mol / L ethanol solution of melamine, tetraethylenepentamine, and ammonium chloride (the mass ratio of the three is 12:19:5), stirring and mixing fully under water bath conditions (50°C), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0066] S5. Freeze the ammonia-modified aerogel matrix at -40°C for 6 hours, then lower the freezing temperature to -60°C and continue freezing for 30 hours to obtain an ammonia-modified fly ash-based aerogel.
[0067] Figure 1 This is the X-ray diffraction pattern of the ammonia-modified fly ash-based aerogel prepared in Example 1. As can be seen from the figure, the ammonia-modified fly ash-based aerogel exhibits an amorphous structure.
[0068] Figure 2 This is a SEM image of the ammonia-modified fly ash-based aerogel prepared in Example 1. It can be seen from the figure that the ammonia-modified fly ash-based aerogel prepared by the present invention has a unique pore structure, showing the characteristics of irregular cubic particles tightly packed with interstitial pores. These rich pore structures can achieve effective adsorption of CO2 molecules on the surface and inside of the aerogel, and increase the interaction time between CO2 molecules and nitrogen-containing functional groups on the aerogel, thereby showing a good carbon capture effect.
[0069] Example 2
[0070] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0071] S1. Weigh 12g of sodium bicarbonate, 10g of sodium acetate and 12g of potassium acetate respectively to prepare an alkali flux, then weigh 20g of fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to the alkali melting temperature of 900°C at a heating rate of 3°C / min, and keep the temperature constant for 1.5h to obtain an alkali-fused fly ash product;
[0072] S2, weigh 5g of alkali-fused fly ash product and add it to 30mL of a mixed acid solution consisting of 3mol / L aqueous solution of citric acid and oxalic acid (the mass ratio of the two is 2:1), stir at room temperature for 4h, and stir at a rate of 300rpm, then separate the solid and liquid to obtain a filtrate;
[0073] S3, weighing 1 mL of 1.2 mol / L urea aqueous solution and adding it to the filtrate obtained in step S2, then placing it in a constant temperature drying oven at 90° C. for gel aging for 6 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0074] S4, weighing 5 g of fly ash-based aerogel, adding it to 20 mL of a mixed ammonia solution of 0.7 mol / L ethanol solution of melamine and tetraethylenepentamine (the mass ratio of the two is 12:19), stirring and mixing fully under water bath conditions (50° C.), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0075] S5. Freeze the ammonia-modified aerogel matrix at -35°C for 8 hours, then lower the freezing temperature to -70°C and continue freezing for 24 hours to obtain an ammonia-modified fly ash-based aerogel.
[0076] Example 3
[0077] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0078] S1. Weigh 17g potassium acetate and 21g magnesium carbonate respectively to prepare an alkali flux, then weigh 20g fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to alkali melting temperature of 800°C at a heating rate of 5°C / min, and keep the temperature constant for 2h to obtain an alkali-fused fly ash product;
[0079] S2, weigh 4 g of alkali-fused fly ash product and add it to 24 mL of a mixed acid solution of 4 mol / L oxalic acid and glacial acetic acid (the mass ratio of the two is 2:1), stir at room temperature for 4 h, and stir at a rate of 250 rpm, then separate the solid and liquid to obtain a filtrate;
[0080] S3, weighing 1 mL of 1.7 mol / L urea aqueous solution and adding it to the filtrate obtained in step S2, and then placing it in a constant temperature drying oven at a temperature of 80° C. for gel aging for 5.5 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0081] S4, weighing 3 g of fly ash-based aerogel, adding it to 12 mL of a mixed ammonia solution of 0.8 mol / L tetraethylene pentamine and ammonium chloride (the mass ratio of the two is 19:5) in ethanol, stirring and mixing them fully under water bath conditions (50° C.), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0082] S5. Freeze the ammonia-modified aerogel matrix at -30°C for 8 hours, then lower the freezing temperature to -60°C and continue freezing for 28 hours to obtain an ammonia-modified fly ash-based aerogel.
[0083] Example 4
[0084] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0085] S1. Weigh 8g of sodium bicarbonate and 28g of magnesium carbonate respectively to prepare an alkali flux, then weigh 20g of fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to the alkali melting temperature of 650°C at a heating rate of 4°C / min, and keep the temperature constant for 1.5h to obtain an alkali-fused fly ash product;
[0086] S2, weighing 5g of alkali-fused fly ash product and adding it to 25mL of 4mol / L citric acid aqueous solution, stirring at room temperature for 6h, the stirring rate is 200rpm, and then solid-liquid separation is performed to obtain a filtrate;
[0087] S3, weighing 1 mL of 2 mol / L urea aqueous solution and adding it to the filtrate obtained in step S2, then placing it in a constant temperature drying oven at a temperature of 100° C. for gel aging for 6 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0088] S4, weighing 2 g of fly ash-based aerogel, adding it to 8 mL of a mixed ammonia solution of 0.9 mol / L tetraethylene pentamine and ammonium chloride (the mass ratio of the two is 19:5) in ethanol, stirring and mixing them fully under water bath conditions (50° C.), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0089] S5. Freeze the ammonia-modified aerogel matrix at -30°C for 8 hours, then lower the freezing temperature to -60°C and continue freezing for 28 hours to obtain an ammonia-modified fly ash-based aerogel.
[0090] Example 5
[0091] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0092] S1. Weigh 12g of sodium bicarbonate, 12g of sodium acetate and 14g of magnesium carbonate respectively to prepare an alkali flux, then weigh 20g of fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to the alkali melting temperature of 750°C at a heating rate of 3°C / min, and keep the temperature constant for 1.5h to obtain an alkali-fused fly ash product;
[0093] S2, weigh 8g of alkali-fused fly ash product and add it to 48mL of 2mol / L oxalic acid aqueous solution, stir at room temperature for 4h, stirring at a rate of 320rpm, then separate the solid and liquid to obtain a filtrate;
[0094] S3, weighing 2 mL of 2.1 mol / L urea aqueous solution and adding it to the filtrate obtained in step S2, then placing it in a constant temperature drying oven at 90° C. for gel aging for 6 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0095] S4, weighing 6 g of fly ash-based aerogel and adding it to 24 mL of 0.8 mol / L ethanol solution of tetraethylenepentamine, stirring and mixing in a water bath (50° C.), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0096] S5. Freeze the ammonia-modified aerogel matrix at -40°C for 8 hours, then lower the freezing temperature to -60°C and continue freezing for 24 hours to obtain an ammonia-modified fly ash-based aerogel.
[0097] Comparative Example 1
[0098] The preparation method of fly ash-based aerogel comprises the following steps:
[0099] S1. Weigh 6g of sodium bicarbonate, 12g of sodium acetate, 9g of potassium acetate and 9g of magnesium carbonate respectively to prepare an alkali flux, then weigh 20g of fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to the alkali melting temperature of 750°C at a heating rate of 4°C / min, and keep the temperature constant for 2h to obtain an alkali-fused fly ash product;
[0100] S2, weighing 5g of alkali-fused fly ash product, adding it to 25mL of a mixed acid solution consisting of 2mol / L aqueous solutions of citric acid, oxalic acid, and glacial acetic acid (the mass ratio of the three is 4:2:1), stirring at room temperature for 5h, the stirring rate is 180rpm, and then solid-liquid separation is performed to obtain a filtrate;
[0101] S3, weighing 1 mL of 1.8 mol / L urea aqueous solution and adding it to the filtrate obtained in step S2, then placing it in a constant temperature drying oven at 90° C. for gel aging for 6 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0102] S4. Freeze the fly ash-based aerogel matrix at -40°C for 6 hours, then lower the freezing temperature to -60°C and continue freezing for 30 hours to obtain fly ash-based aerogel.
[0103] Comparative Example 2
[0104] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0105] S1, weigh 5g of fly ash and add it to 25mL of a mixed acid solution of 2mol / L of citric acid, oxalic acid and glacial acetic acid (the mass ratio of the three is 4:2:1), stir at room temperature for 5h, and stir at a rate of 180rpm, then separate the solid and liquid to obtain a filtrate;
[0106] S2, weighing 1 mL of 1.8 mol / L urea aqueous solution and adding it to the filtrate obtained in step S1, then placing it in a constant temperature drying oven at 90° C. for gel aging for 6 h, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0107] S3, weighing 5g of fly ash-based aerogel and adding it into 20mL of a mixed ammonia solution of 0.8mol / L ethanol solution of melamine, tetraethylenepentamine and ammonium chloride (the mass ratio of the three is 12:19:5), stirring and mixing fully under water bath conditions (50°C), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0108] S4. Freeze the ammonia-modified aerogel matrix at -40°C for 6 hours, then lower the freezing temperature to -60°C and continue freezing for 30 hours to obtain an ammonia-modified fly ash-based aerogel.
[0109] Comparative Example 3
[0110] The preparation method of ammonia-modified fly ash-based aerogel comprises the following steps:
[0111] S1. Weigh 6g of sodium bicarbonate, 12g of sodium acetate, 9g of potassium acetate and 9g of magnesium carbonate respectively to prepare an alkali flux, then weigh 20g of fly ash and add it to the prepared alkali flux, grind it evenly and put it into a tube furnace, heat it from room temperature to the alkali melting temperature of 750°C at a heating rate of 4°C / min, and keep the temperature constant for 2h to obtain an alkali-fused fly ash product;
[0112] S2, weighing 5g of alkali-fused fly ash product, adding it to 25mL of a mixed acid solution consisting of 2mol / L aqueous solutions of citric acid, oxalic acid, and glacial acetic acid (the mass ratio of the three is 4:2:1), stirring at room temperature for 5h, the stirring rate is 180rpm, and then solid-liquid separation is performed to obtain a filtrate;
[0113] S3, placing the filtrate obtained in step S2 in a constant temperature drying oven at a temperature of 90° C. for gel aging for 6 hours, and then washing with deionized water for deacidification to obtain a fly ash-based aerogel matrix;
[0114] S4, weighing 5 g of fly ash-based aerogel, adding it to 20 mL of a mixed ammonia solution of 0.8 mol / L ethanol solution of melamine, tetraethylenepentamine, and ammonium chloride (the mass ratio of the three is 12:19:5), stirring and mixing fully under water bath conditions (50°C), and obtaining an ammonia-modified aerogel matrix after uniform mixing;
[0115] S5. Freeze the ammonia-modified aerogel matrix at -40°C for 6 hours, then lower the freezing temperature to -60°C and continue freezing for 30 hours to obtain an ammonia-modified fly ash-based aerogel.
[0116] Test example
[0117] The aerogels prepared in Examples 1-5 and Comparative Examples 1-3 were tested for carbon dioxide adsorption performance in the following manner:
[0118] The aerogel sample (5 mg) was placed in a thermogravimetric analyzer, and nitrogen was first introduced, and the temperature was raised to 110°C at a heating rate of 10°C / min for pretreatment for 2h, and then the temperature was lowered to the adsorption temperature of 40°C, and carbon dioxide was introduced for an adsorption time of 120min, wherein the nitrogen and carbon dioxide gas flow rates were 80mL / min and 20mL / min, respectively. The results are shown in Table 2.
[0119] Table 2
[0120] sample Carbon dioxide adsorption capacity (mmol / g) Example 1 3.49 Example 2 3.37 Example 3 3.28 Example 4 3.03 Example 5 3.01 Comparative Example 1 0.61 Comparative Example 2 1.54 Comparative Example 3 2.13
[0121] It can be seen from the data in Table 1 that the aerogels prepared in Examples 1-5 of the present invention have a good adsorption effect on carbon dioxide. By comparing the carbon dioxide adsorption of the fly ash-based aerogels prepared in Example 1 and Comparative Example 1, it can be seen that the adsorption of Example 1 is more than 5 times that of Comparative Example 1, and the fly ash-based aerogels modified by ammonia have a significant carbon dioxide adsorption effect; by comparing the carbon dioxide adsorption of the ammonia-modified fly ash-based aerogels prepared in Example 1 and Comparative Example 2, it can be seen that the carbon dioxide capture performance is effectively improved after the fly ash is alkali-melted in Example 1. This is because the high-temperature alkali-melting process strengthens the aerogel pore formation and increases the specific surface area of the adsorbent; by comparing the carbon dioxide adsorption of the ammonia-modified fly ash-based aerogels prepared in Example 1 and Comparative Example 3, it can be seen that after the fly ash filtrate is dripped with urea aqueous solution in Example 1, the aerogel precipitation and complexation are more complete, which effectively improves the carbon dioxide capture performance and is more conducive to adsorption.
[0122] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0123] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing ammonia-modified fly ash-based aerogel, characterized in that the steps include: Grinding and mixing fly ash and alkali flux, and subjecting the mixture to alkali fusion treatment to obtain alkali fused fly ash product; adding the alkali-fused fly ash product into an acid solution, stirring and hydrolyzing, and obtaining a filtrate after solid-liquid separation; Adding urea aqueous solution to the filtrate, aging and washing, to obtain a fly ash-based aerogel matrix; The fly ash-based aerogel matrix is mixed with an ammonia solution and subjected to a modification treatment to obtain an ammonia-modified aerogel matrix; The ammonia-modified aerogel matrix is subjected to graded freeze drying to obtain the ammonia-modified fly ash-based aerogel.
2. The preparation method according to claim 1, characterized in that The mass ratio of fly ash to alkali flux is 1:1.7-1.9; and / or, The alkali fusion treatment temperature is 650-900°C, the heating rate is 3-5°C / min, and the holding time is 1.5-2h; and / or, The alkali flux includes at least one of sodium bicarbonate, sodium acetate, potassium acetate and magnesium carbonate.
3. The preparation method according to claim 1, characterized in that: The acid solution comprises an aqueous solution of at least one of citric acid, oxalic acid and glacial acetic acid; and / or, The concentration of the acid solution is 2-4 mol / L; and / or, The solid-to-liquid ratio of the alkali-fused fly ash product to the acid solution is 1:5-6; and / or, The stirring hydrolysis time is 4-6 hours, and the stirring rate is 180-320 rpm.
4. The preparation method according to claim 1, characterized in that: The concentration of the urea aqueous solution is 1.2-2.1 mol / L; and / or, The volume ratio of the filtrate to the urea aqueous solution is 25:
1.
5. The preparation method according to claim 1, characterized in that: The aging time is 5-6 hours and the temperature is 80-100°C.
6. The preparation method according to claim 1, characterized in that: The ammonia solution is an ethanol solution of at least one of melamine, tetraethylenepentamine and ammonium chloride; and / or, The concentration of the ammonia solution is 0.7-0.9 mol / L.
7. The preparation method according to claim 6, characterized in that: The solid-to-liquid ratio of the fly ash-based aerogel matrix to the ammonia solution is 1:
4.
8. The preparation method according to claim 1, characterized in that: The step of graded freeze drying comprises: freezing at -30°C to -40°C for 6-8 hours, and then freezing at -60°C to -70°C for 24-30 hours.
9. An ammonia-modified fly ash-based aerogel, characterized in that: The ammonia-modified fly ash-based aerogel is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the ammonia-modified fly ash-based aerogel as claimed in claim 9 in carbon dioxide capture.
Citation Information
Patent Citations
Method for preparing SiO2-Al2O3 composite aerogel material from fly ash
CN110668452A
Composite modified functional pig manure carbon and preparation method thereof
CN111644149A
Method for preparing CO2 adsorbent by using coal-fired solid waste fly ash
CN114904479A
Controllable hierarchical pore solid amine adsorbent based on fly ash base, preparation method of adsorbent and application of adsorbent in CO2 trapping
CN119075924A